ANALYSIS OF WALL SHEAR PARAMETERS OF PHYSIOLOGICAL PULSATILE FLOW THROUGH MILD AND SEVERE ARTERIAL STENOSIS AND CORRELATION TO ATHEROSCLEROSIS - Goswami, Partha; Mandal, Dipak Kumar; Manna, Nirmal Kumar; Chakrabarty, Somnath (MATTER: International Journal of Science and Technology, 2016)
Numerical simulations of physiological pulsatile flow through mild and severe arterial stenosis are carried out to analyze wall shear stress parameters. The governing equations are solved by finite volume method. The study shows that the distribution patterns of time-averaged wall shear stress (TAWSS), oscillatory shear index (OSI) and relative residence time (RRT) are same forboth mild stenosis and severe stenosis. The magnitude of peak TAWSS and low TAWSS and extent of negative TAWSS of severe stenosis is higher than those of mild stenosis. The OSI value of severe stenosis is higher at distal to throat of stenosis in comparison to mild stenosis. The size of recirculation zone of severe stenosis is lager than that of mild stenosis. The abnormally high peak value of RRT of severe stenosis is concentrated and located at far away from stenosis when it is compared with mild stenosis.